Swallowing and Temporomandibular Disorders in Adults. Issue 3 (May 2018) - Ciavarella, Domenico; Tepedino, Michele; Laurenziello, Michele; Guida, Laura; Troiano, Giuseppe; Montaruli, Graziano; Illuzzi, Gaetano; Chimenti, Claudio; Lo Muzio, Lorenzo
Abstract : Introduction: Temporomandibular disease (TMD) etiology is multifactorial and is related to many perpetuating, predisposing, and initiating factors. The daytime parafunctions may have an important role in TMD pathogenesis. The most frequent parafunctions analyzed were the static parafunction (ie, clenching) and the dynamic parafunction (ie, grinding). In the present paper, the authors evaluated the swallowing (an oral function/parafunction) with the surface electromyography in patients with TMD. Materials and Methods: Twenty patients with TMD problems (nonhealthy patients, NHP) (mean age: 33 ± 1.994; 8 men and 12 women) and 20 healthy matched subjects (HP) (34.4 ± 2.782; 6 men and 14 women) were selected and examined. On each patient, an 8-channel surface electromyography was done during saliva swallowing. Results: Nonhealthy patients presented higher masseter and temporalis activation ( P  < 0.05) and an unbalancing of temporalis and submental muscles activation ( P  < 0.05) than the HP. Discussion: Nonhealthy patients presented a time of swallow higher than HP ( P  < 0.001). Nonhealthy patients presented a higher muscles activation and time of swallow than HP and a decrease of muscles balancing activation.